Poverty and sustainable livelihoods in the seasonally submerged haor area of Netrokona District, Bangladesh / Talukder Golam Rabby - Rabby, Talukder Golam (2012)
Being geographically remote, ecologically vulnerable and environmentally isolated, poverty is severe and livelihood is onerous in the northeastern Haor area in Bangladesh. Thus, this research which explores the nexus of poverty and livelihood in the Haor area focuses on four specific objectives: characterizing poverty and the poor, causes and consequences of poverty; examining the income determinants of the poor households; exploring the dynamics of poverty and the impact of seasonal domestic migration of the poor on poverty. A mixed methodology of research is applied to analyze the cross-sectional primary data collected through field surveys. The results demonstrate that the incidence of income poverty is 73% among the sample households of which 29% and 44% can be considered the moderately and extremely poor, respectively. The poor are primarily uneducated, landless, unemployed and female-headed households with the latter two groups constituting the extremely poor strata. The household income of the poor households is highly influenced by public credit accessibility, remittances (by migrant household members), dry season income, household size, employment status and age of household head. The poverty dynamics reveal that the exposure of resource pauperization to poverty has increased overtime in the Haor area. The monsoonal deluge (in the wet season), mono-cropping, flashfloods, seasonal unemployment, capital deficiencies and policy weaknesses are among the most important causes of poverty in the Haor area. The poor who are uneducated and capital deficient resort to seasonal domestic migration as an income diversifying strategy but one which is largely ineffective. Persistent poverty has serious consequences on the livelihood strategies of the poor; as current poverty reduction strategies in the Haor area have limited impact, there is a need to examine and formulate appropriate policy interventions aimed at generating steady sources of income for the poor households. Among others, they include revitalizing Haor agriculture, establishing non-farm sector work opportunities (handicrafts, transportation, communication, storage services, etc), investment in infrastructure facilities and cooperative activities. The theoretical and empirical findings of this research can provide inputs for policymakers to create a long term framework for poverty reduction and sustainable livelihood development for the poor households in the Haor area of Bangladesh.